Prosedur Perwalian, Hak dan Kewajiban Para Pihak Serta Faktor Penghambat dalam Pelaksanaan Perwalian Anak oleh Panti Asuhan Eugene Schmiz di Kelurahan Lewoleba Timur Berdasarkan Hukum Perdata (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Guardianship is the authority in the maintenance and supervision of minors, who are not under the authority of their parents and the management of the objects or assets of the child that have been regulated by law. In the implementation of child guardianship there are procedures that regulate it, but in reality the Eugene Schmitz Orphanage implements the rules in its own way. The formulation of the problem: (1) What are the procedures for child guardianship at the Eugene Schmitz Orphanage in Lewoleba Timur Village based on civil law? (2) What are the rights and obligations of the parties in the implementation of child guardianship at the Eugene Schmitz Orphanage in Lewoleba Timur Village based on civil law? (3) What are the inhibiting factors in the implementation of child guardianship at the Eugene Schmitz Orphanage, Lewoleba Timur Village?. The objectives of this research are: (1) To Know the Procedure of Child Guardianship at the Eugene Schmitz Orphanage in Lewoleba Timur Village Based on Civil Law. (2) To Know the Rights and Obligations of the Parties in the Implementation of Child Guardianship at the Eugene Schmitz Orphanage in Lewoleba Timur Village Based on Civil Law. (3) To find out the inhibiting factors in the implementation of child guardianship at the Eugene Schmitz Orphanage in Lewoleba Timur Village. The benefit of this research is to add information for the government to better supervise guardianship procedures and add information to the public to find out the child guardianship procedure. The method used in this research is empirical juridical legal method. The results showed that: (1) The procedure for implementing child guardianship at the Eugene Schmitz Orphanage applies its own rules which are simple, straightforward, do not require a lot of money and do not require a long time so that both the orphanage management, caregivers and children who enter know about the procedure and help parents in the administrative process. (2) The rights and obligations of the parties to the Orphanage arise as a result of the responsibility for their respective roles, although it has been well implemented, in fact there are problems that arise resulting in unbalanced rights and obligations. (3) The inhibiting factors experienced in the implementation of guardianship are ignorance of guardianship procedures, lack of entry requirements and children who enter without biological parents. The conclusions in this study are (1) The child guardianship procedure at the Eugene Schmitz Orphanage does not apply the rules in accordance with the Provisions of the Law. (2) The rights and obligations of the parties are balanced as a result of responsibility for their respective roles. (3) The inhibiting factors in the implementation of guardianship are ignorance of procedures, lack of files/documents and unclear identity of the child. The author's suggestion is the need for socialization from the government to orphanage administrators and the community regarding child guardianship procedures in accordance with the provisions of the Law.